Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Teachers’ Learning Communities for Developing High Order Thinking Skills—A Case Study of a School Pedagogical Change - Miedijensky, Shirley; Sasson, Irit; Yehuda, Itamar (Interchange (Toronto. 1984), 2021)
This study deals with an elementary school that is undergoing a process of pedagogical change. The teachers understood that their weak point was excessive use of teaching based on memorization rather than developing high-order thinking (HOT) skills. The school therefore established teachers’ learning communities for peer learning and designing learning tasks that encourage the development of HOT skills. Quantitative and qualitative research tools were used in this study as a formative assessment. The data included learning tasks and interviews with teachers. The findings indicate an increase in the expression of critical thinking and the cognitive levels of application, analysis, and synthesis. The national test scores indicate an increase in students’ performance in most subjects. It appears that educators recognize the need for a transition from teaching that emphasize memorizing information to methods that develop students’ thinking skills and independent learning and initiated a successful pedagogical change.
Keywords: Case studies; Collaboration; Critical thinking; Education; Educational Philosophy; Educational Policy and Politics; Elementary schools; Formative assessment; High-order thinking; Learning; Memorization; Pedagogical change; Pedagogy; Peer learning; Qualitative research; Teachers; Teachers’ learning communities; Teaching; Teaching methods; Test scores; Thinking skills

Brazil Case Study - Mello, Ursula; Loureiro, Andre; Cruz, Louisee (World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.
Keywords: Education; Education Equity; Education Finance; Education Outcomes; Education Spending; Fiscal Decentralization; Fiscal Transfers; Public Expenditure

Emergency remote teaching and students’ academic performance in higher education during the COVID-19 pandemic: A case study - Iglesias-Pradas, Santiago; Hernández-García, Ángel; Chaparro-Peláez, Julián; Prieto, José Luis (Computers in Human Behavior, 2021)
The COVID-19 pandemic has caused a massive disruption in the way traditional higher education institutions deliver their courses. Unlike transitions from face-to-face teaching to blended, online or flipped classroom in the past, changes in emergency remote teaching –a temporary shift of instructional delivery to an alternate remote delivery mode due to crisis circumstances– happen suddenly and in an unplanned way. This study analyzes the move to emergency remote teaching at the School of Telecommunication Engineering (Universidad Politécnica de Madrid), and the impact of organizational aspects related to unplanned change, instruction-related variables –class size, synchronous/asynchronous delivery– and use of digital supporting technologies, on students' academic performance. Using quantitative data of academic records across all (N = 43) courses of a bachelor's degree programme in Telecommunication Engineering and qualitative data from a questionnaire delivered to all (N = 43) course coordinators, the research also compares the academic results of students during the COVID-19 pandemic with those of previous years. The results of this case study show an increase in students' academic performance in emergency remote teaching, and support the idea that organizational factors may contribute to successful implementation of emergency remote teaching; the analysis does not find differences across courses with different class sizes or delivery modes. The study further explores possible explanations for the results of the analysis, considering organizational, individual and instruction-related aspects.

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

The impact of online learning as emerging technology on parents: Case study of parents of primary school children in Nairobi, Kenya. - Emmanuel, Jadesola; Oduor, Collins (Journal of Language, Technology & Entrepreneurship in Africa, 2021)
Kenya, as a nation has a stable schooling system based on synchronous classroom learning. The advent of the COVID 19 pandemic has led to the sudden shift in paradigm to remote schooling learning systems. Several studies have been carried out on remote schooling systems and the impact of parent’s involvement in children’s remote school, but none has been sighted on its impact on parents. The objective of this study was to determine the impact of the sudden paradigm shift on parents of remote schooling pupils in Kenya during this pandemic. A descriptive survey design was utilized. Primary data was collected by online questionnaires and secondary data from past studied. The analysis was done with a statistical application. It was found out that, remote schooling may be easily accepted by many Kenyan parents with 39.8% of parents indicating that they will recommend remote schooling having indicated some benefits derived from it and 24.8% indicating that they will not. It was therefore recommended that the national government should address factors that may hinder effective remote learning, thus encouraging parental involvement and support. It was also recommended that the government and education practitioners should officially develop and implement standards and curriculum for the implementation of remote learning in Kenya in preparation for future pandemics. Keywords: remote schooling, remote learning, descriptive survey design
Keywords: ⛔ No DOI found

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Educational technology to improve capacity - integrating adaptive programmes in public schools in Kenya - Kaye, Tom (2021)

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Case Study: TEAM Girl Malawi - Link Education International (2021)

Case study: Team Girl Malawi - Link Education International (2021)

Case study: Sisters for Sisters' Education - GEC (VSO, 2021)

Case Study: Sisters for Sisters’ Education - VSO (2021)

Gender-Transformative Programming in UNICEF Selected Case Studies - Marcus, Rachel; Samuels, Fiona; Belachew, H; Jalal, S (2021)
Reflections and Lessons for UNICEF’s Gender Policy and Action Plan (2022-2025), A compendium of papers, Florence: UNICEF Innocenti Research Centre

Case Study: GEARR-ing Up for Success After School - PEAS (2021)

Use of learning assessment data in the planning cycle. Case study – Ghana - Begue-Aguado, Alberto (United States Agency For International Development (USAID), 2021)

The future of language education in Europe: case studies of innovative practices - Le Pichon-Vorstman, Emmanuelle; Siarova, Hanna; Szőnyi, Eszter (European Journal of Language Policy, 2021)

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Strengthening education management information systems for increased resilience to crises: A synthesis of case studies - UNESCO (UNESCO, 2021)

Framework for Teacher Support During Remote Teaching in a Crisis: COVID-19, as a Case Study - Denden, Mouna; Tlili, Ahmed; Burgos, Daniel; Jemni, Mohamed; Huang, Ronghuai; Essalmi, Fathi; Chang, Ting-Wen (Radical Solutions for Education in a Crisis Context, 2021)

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Strengthening Education Management Information Systems (EMIS) and Data for Increased Resilience to Crisis: country case study: South Soudan - Mwaniki, David (UNESCO, 2021)
Keywords: auto_merged

Case Study: Building Girls to Live, Learn, Laugh and ‘SCHIP’ in Strong, Creative, Holistic, Inclusive, Protective, Quality Education - CRANE and Viva (2021)

Strengthening Education Management Information Systems (EMIS) and Data for Increased Resilience to Crisis: country case study: Uganda - UNESCO Digital Library - Sparkes, James (UNESCO, 2021)

Situation analysis on the effects of and responses to COVID-19 on the Education Sector in Asia: Bhutan case study - UNESCO Digital Library - UNESCO (2021)

Endogenous development in Lao PDR in the era of globalization: Contrastive case studies of external assistance for a sustainable rural development path - Vongxay, Phonemany; Suzuki, Noriyuki (Journal of Mekong Societies, 2021)
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Situation Analysis on the Effects of and Responses to COVID-19 on the Education Sector in Asia - UNICEF & UNESCO (2021)
Case Study from Pakistan

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Cascade Teacher Training Model in Disaster Education: A Case of Turkey - Gökmenoğlu, Tuba; Sönmez, Elif Daşçı; Yavuz, İbrahim (2021)
Individuals' reluctance to take precautions before the disasters happen is one of the most critical concerns of the disaster management area. The disaster education given through schools is a critical process in addressing this problem. The purpose of this paper is to introduce the teacher training program model and the implementation practices of Turkey's School-Based Disaster Education Project. In Turkey, there are few studies regarding the planning, development, implementation, and evaluation stages of Disaster Risk Reduction education for teachers. The project has been carried out within the framework of the Ministry of National Education and Japan International Cooperation Agency. An at-scale cascade teacher professional development model was implemented. The model reached 135,375 teachers in 67 provinces by the 567 trainer teachers in a relatively short time with the cascade training system. This project has brought a significant nationwide disaster risk reduction training experience for Turkey with its economic and sustainable structure.

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The Views of University Students About the Achievements and Motivations of the Distance Education Process During the Pandemic Period - Güldal Kan, Şebnem; Çaltıkuşu, Çilem; Şensoy, Şeniz (Propósitos y Representaciones, 2021)
The aim of this study is to examine the views of students about the achievements and motivations of thedistance education processes in universities during the pandemic period. The working group consists of 68 prospective teachers who continue their undergraduate programs in different departments of a private university in Northern Cyprus in the 2019-2020 spring academic year. All these participantsarestudying at thevariousdepartments of theFaculty of Education as 17 are in Pre-school Education, 28 in PrimaryEducationMathematics, 6 in PrimaryEducation, 1 in HistoryTeaching, 12 in Special Needs Education, 4 of them arestudying in Guidance and Psychological Counseling. The study is a qualitative study and the design of the study is determined as a case study. 42 female and 26 male teacher candidates participated in the study group. The majority of the participants are prospective teachers studying in their final year at university. While choosing the participants, easily accessible case sampling from purposeful sampling type was used. A Semi-structured interview form was used as a toolfordata collection. Later, the opinions of the experts were obtained and the interview questions were re-arranged accordingly and applied to the participants. As a result of the research, it was concluded that the psychological trauma experienced by teacher candidates during distance education at thepandemicperiodaffects both the success and motivation of their lessons.

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan,; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Role of Intergovernmental Fiscal Transfers in Improving Education Outcomes - Al-Samarrai, Samer; Lewis, Blane (World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.
Keywords: Education; Education Equity; Education Finance; Education Outcomes; Education Spending; Fiscal Decentralization; Fiscal Transfers; Public Expenditure

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

The Effects of Micro-Reflective Teaching Practices on the Professional Skill Development of Pre-Service Physics Teachers - Batman, Demet; Saka, Ahmet Zeki (The Turkish Online Journal of Educational Technology, 2021)
The aim of this study is to find out the effects of micro-reflective teaching practices on the professional skill development of pre-service physics teachers. It was planned as an experimental study with one group pretestposttest and supported by the case study method. The data were collected by using professional skill scale, observation form and reflective diaries. The sample of the study composed of 13 (6 female, 7 male) pre-service teachers were studying in a Physics Teaching Program in an education faculty in north-eastern Turkey. Each preservice teacher implemented 5 micro-reflective teaching practice within the scope of the research. These practices were recorded by the camera. At the end of each practice pre-service teachers watched themselves and wrote their reflective diaries. The data obtained from the scales and the observation form were analyzed by using the Wilcoxon Signed Rank Test, and the data acquired from the reflective diaries were examined based on interpretive analysis. The findings based on the data obtained from the professional skill scale, observation forms and the reflective diaries indicate that micro-reflective teaching practices help improve pre-service physics teachers’ basic professional skills; subject matter mastery, planning, communication, classroom management, and evaluation.
Keywords: ⛔ No DOI found

Computer-assisted instruction tools: A model to guide use in low-and middle-income countries - Kaye, Thomas; Ehren, Melanie (International Journal of Education and Development using Information and Communication Technology, 2021)
Learning outcomes in low- and lower-middle-income countries (LMICs) require significant improvement. With traditional reform efforts taking many years to realise results, education practitioners in LMICs are searching for innovative ways to rapidly strengthen learning outcomes. One tool showing promise is computer-assisted instruction (CAI). While a growing number of studies document CAI’s positive impacts on learning outcomes, others have found nil or negative effects. Research has yet to identify why these differences occur, and, most importantly, which factors must be in place to ensure that CAI contributes to improving learning outcomes. The aim of our research was to fill this gap in the research by developing a model highlighting those factors influencing the results of CAI interventions. Adopting a realist-informed methodology, we analysed 21 resources shared by 13 experts from around the world. We used the results of this analysis to develop a model that outlines key trends that facilitate and/or impede the deployment of CAI tools in LMICs. We find that key factors that should be considered when designing CAI interventions include the operating environment; stakeholder engagement; infrastructure; technological trust; CAI tool design; content curation/creation; student engagement; classroom integration; teacher capacity; student capacity; and data collection and use. This model highlights both these individual elements as well as noting how these elements interact. The model provides a foundation that can guide future research in this under-examined area.
Keywords: ⛔ No DOI found

From face-to-face to teaching at a distance: Lessons learned from emergency remote teaching - Corcuera, Lovely; Abel Alvarez, Jr (Asian Journal of Distance Education, 2021)
The Covid-19 disrupts not only the health, economic, and tourism sectors but it paralyzed the education sector as well. Since face-to-face teaching and learning environment is still not possible in the Philippine context, this phenomenon leaves the teachers to use various alternative ways of instructional delivery. The sudden shift of teaching and learning delivery continuously challenges not only the students but also the teachers who are serving as educational front liners at the time of the pandemic crisis. The lack of proper training and experiences of teachers in online teaching and distance education served as educational loopholes in the context of emergency remote education.  Hence, this case study attempts to explore the experiences of K-12 senior high school teachers who have been immersed in emergency remote teaching. In analyzing the data gathered, the descriptive coding process was used. Interestingly, there were three themes reported in this study: getting the right mix of instructional methods, engaging in different open educational resources and information, and highlighting the need for the pedagogy of care and understanding. Although this study does not aim to make any generalities, however, the researchers saw the need to understand and investigate the journey of the K-12 senior high school teachers, which are essential in providing lending ears about their transitioning experiences from the traditional classroom environment to emergency remote education. This study concludes with the implications of the findings that emerged and the direction for further research.
Keywords: Covid-19; K-12 teachers; distance education; emergency remote education; teaching modality; ⛔ No DOI found

Goodhart’s Law and the gaming of UK public spending numbers - Hood, Christopher; Piotrowska, Barbara (Public Performance & Management Review, 2021)
Goodhart’s Law, originally inspired by money-supply indicators, predicts high-consequence administrative numbers tend to be gamed out of meaningfulness. This paper argues that, in addition to the well-documented manipulation of aggregate input numbers at the top-levels of decision making and performance indicators used for output control at the lower level, meso-level gaming happens also on the input side of public expenditure planning and control. A key mechanism through which it operates is creative categorization in the classification of units of spending. Based on a UK study, we explore three questions: can we find evidence for the existence of gaming in public expenditure control, how does the creative categorization work and how material or consequential is it? Using case studies of “protected” spending, public-private partnerships and accounting changes, we show that gaming understood as creative categorization is readily observable in UK public expenditure control and Goodhart’s Law effects can indeed be material or consequential, both in scale and in their implications for government accountability. We conclude that creating new spending categories to control public expenditure and limit gaming is a two-edged sword since it itself creates new opportunities for gaming.
Keywords: Goodhart’s Law; creative categorization; fiscal illusions; gaming; public finance management; public spending; rule bending

What drives successful economic diversification in resource-rich countries? - Lashitew, Addisu A; Ross, Michael L; Werker, Eric (The World Bank Research Observer, 2021)
The “resource curse” is often understood to imply poor growth in the non-resource sectors of the economy, but research into the diversification performance of resource-rich countries is limited. This paper surveys recent evidence and identifies empirical patterns in the economic diversification of resource-rich countries. Diversification is measured using the growth of per capita non-resource (manufacturing and services) sectors in domestic and export markets, which has a cleaner interpretation than competing measures. This measure is used to evaluate the long-term diversification of countries that started off as resource-dependent, and to rank countries according to their performance. We then identify policy-relevant correlates of diversification at the national level, including the acquisition of human capital, public and intellectual capital, and firm dynamism. More resource-dependent countries appear to perform worse on measures of human capital and intellectual capital, but more resource-abundant countries perform better on public capital and human capital accumulation. We examine the mechanisms behind diversification performance through in-depth case studies of Oman, Laos, and Indonesia, and conclude by identifying policy lessons and future research directions.
Keywords: ⛔ No INSPIRE recid found

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Timor-Leste education: Supporting sustainable system-wide reform and school leader capacity-building through collaborative foreign aid - Owen, Susanne; Wong, Debbie (Journal of Educational Change, 2021)
Effective school leadership and ongoing teacher capacity-building are essential aspects of school reform and improving educational outcomes for students in developing countries. This paper examines a Timor-Leste curriculum reform and associated school leader capacity-building and the implementation processes for building sustainability, within the context of research literature regarding effective professional development and successful foreign aid principles. The Timor-Leste leadership program was developed using an interpretivist paradigm and action research, with the authors being program designers and managers embedded in the context. School leader interviews and surveys, meeting notes and monitoring and evaluation reports, also teacher skills and student achievement data, were continuously examined to analyse issues and plan actions and solutions. Findings outline early impacts in relation to changing school leader behaviours, improved teacher skills and increased student literacy and numeracy, while also presenting implementation processes and actions taken to overcome challenges in relation to research-informed foreign aid principles.Given the importance of foreign aid for supporting significant educational improvement in developing countries, this Timor-Leste leadership capacity-building case study provides an example relevant to an under-researched area. While the focus is on one particular country and reform involving curriculum and professional development, the paper has value for other education contexts and system change initiatives which involve collaborations with foreign aid donors.
Keywords: Foreign aid; International development; School leadership capacity-building; School reform; School-based professional development; ⛔ No INSPIRE recid found

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

A Global Mapping of Delivery Approaches - Mansoor, Zahra; Qarout, Dana; Anderson, Kate; Carano, Celeste; Dvorakova, Veronika; Williams, Martin J (2021)
The past 25 years has seen numerous governments worldwide adopting new institutional forms, such as delivery units and reform labs, to try to improve service delivery. We conduct a systematic global search and mapping of these delivery approaches. We identify 152 instances of delivery approach (DA) adoption from 80 diﬀerent countries, ranging from the center of government down to provincial and local levels, with an accelerating trend of adoption since 2010. The majority of these include education as a focus sector. The main ﬁnding that emerges from our analysis is that there is no single model that characterizes the design of such approaches or the purposes for which they are adopted. However, we do identify a number of patterns, including that DAs in lower-income countries are more likely to focus mainly on output-type goals (as opposed to outcomes), use external consultants, and utilize accountability- and incentive-driven mechanisms relatively more heavily than their counterparts in middle- and high-income countries. While our ﬁndings are purely descriptive and cannot be used to infer whether DAs are eﬀective, they give an indication to policymakers about the menu of potential options available to them in designing DAs. This global mapping can also provide useful context for existing and future country-level case studies that investigate the eﬀectiveness of DAs and seek to explore which designs might be more eﬀective in diﬀerent contexts and for diﬀerent purposes.
Keywords: ⛔ No DOI found

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

A Framework to Democratise the Design of Educational Games on Social Issues during Game Jams - Myers, Christina (The Open University, 2021)
Game Jams are events organised to create computer games, usually taking place during weekends. These events have become a popular way to enable participants to experience processes and practices of game development as well as to offer multidisciplinary learning opportunities, accessed through the variety of skills involved in game design. However, these events tend to be attended predominantly by male game developers and present barriers to participation for more diverse groups. This thesis investigates how to support diverse group participation in Game Jams, including people from different ethnicities, genders, ages, sexual orientations and who do not have any prior experience of designing games; and explores Game Jam participation as an opportunity to discuss social issues. To this end, a framework to democratise the design of educational games on social issues in Game Jams is proposed. The framework consists of a process with structured resources and activities to enhance learning by supporting egalitarian participation and agency. It offers collaborative learning opportunities for groups to engage with a social issue, relying on storytelling and on the exchange of perspectives and experiences. It also provides support and access to research-based principles to design games for education, and egalitarian opportunities to acquire game development skills, considered relevant opportunities given the wide-spread use of games and increasing interest in games as engaging tools for online education. The development of the framework is grounded in Critical Pedagogy, an educational approach providing principles and processes to democratise learning initiatives based on egalitarian participation and agency. Following a Design-Based Research methodology, the framework is developed through a case study on creating educational games on everyday sexism. A set of formative design studies are undertaken to co-design resources and activities that enable participants to elaborate solutions to the social issue and create educational games themselves. An evaluative study is then presented with the realisation of two Game Jams to assess and validate the proposed framework. The theoretical contributions of this work validate two new applications of Critical Pedagogy. The first one is to apply Critical Pedagogy to shape Game Jams to enhance learning through the active involvement of participants as equal learners and agents of social change. The second one applies Critical Pedagogy to democratise knowledge of design principles to create educational games on social issues. Lastly, access to a co-created tool for raising awareness of everyday sexism and insights on how to enable broad audiences to acquire games development skills are some of the practical contributions of this thesis.

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon,; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found